PEMBANGUNAN APLIKASI PEMBELAJARAN M-SPWTC UNTUK KURSUS PEMASANGAN DAN PENYELENGGARAAN ELEKTRIK SATU FASA - Subramaniam, Tamil Selvan; Ariffin, Arihasnida; Hamzah, Norhasyimah; Rubani, Siti Nur Kamariah (Online Journal for TVET Practitioners, 2018)
The use of mobile learning as a learning resource is widespread in today's teaching and learning. However, the problem exists is that there is no mobile learning based learning application ever developed or provided for the needs of vocational college students in the One Phase Electrical Installation and Maintenance course, specifically for a one-phase electrical testing topic. Therefore, the purpose of the M-SPWTC learning application based on this android platform is to be used as a learning support material and to enhance student understanding in the One Phase Electrical Installation and Maintenance course. The objective of this study is to develop and evaluate the suitability of the elements found in M-SPWTC learning applications and to identify students' acceptance of M-SPWTC learning applications. The design of this study is product development using ADDIE model and quantitative study method. A total of 30 vocational college students and 4 specialists were selected as respondents in this study using questionnaire instruments that were analyzed using the Statistical Packages for the Social Science (SPSS) version 20 for frequency, percentage, and mean. Overall, the M-SPWTC learning application was successfully developed and adopted. Evaluation findings also show that elements integrated in M-SPWTC meet the needs of use such as the use of text, video, animation and graphics and are accepted by students as support materials in learning. The findings of this study can be used as a guide to designing online learning content, especially in the field of TVET.